2009
DOI: 10.1016/j.jpowsour.2008.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of carbon fuels for direct carbon fuel cells

Abstract: a b s t r a c tThe direct carbon fuel cell (DCFC) is a promising power-generation device that has much higher efficiency (80%) and less emissions than conventional coal-fired power plants. Two commercial carbons (activated carbon and carbon black) pre-treated with HNO 3 , HCl or air plasma are tested in a DCFC. The correlation between the surface properties and electrochemical performance of the carbon fuels is explored. The HNO 3 -treated carbon fuels have the highest electrochemical reactivity in the DCFC du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 27 publications
6
128
0
Order By: Relevance
“…From the XPS results, the Adaro char has the highest surface oxygen content, while the Openblue char shows the lowest value. In spite of the insufficiency of the carbon concentration, the higher oxygen to carbon rate of Adaro char promote the electrochemical reactions [8]- [11]. Since Openblue char had low amount of oxygen, the potential cannot be maintained at the high current density which requires a lot of electron transfer.…”
Section: The Effect Of Fuel Properties On Electrochemical Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the XPS results, the Adaro char has the highest surface oxygen content, while the Openblue char shows the lowest value. In spite of the insufficiency of the carbon concentration, the higher oxygen to carbon rate of Adaro char promote the electrochemical reactions [8]- [11]. Since Openblue char had low amount of oxygen, the potential cannot be maintained at the high current density which requires a lot of electron transfer.…”
Section: The Effect Of Fuel Properties On Electrochemical Reactionmentioning
confidence: 99%
“…Considering CO production, the alternative electrochemical mechanism was proposed at high temperature in molten carbonate [8].…”
Section: Fuel Gasificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the SECA program, there has been significant effort in the USA, developing an integrated coal gasification solid oxide fuel cell system [41]. A number of detailed system modelling studies have shown that, in principle, it is possible to achieve an overall system efficiency of over 45% for an atmospheric pressure coal gasification fuel cell system and around 60% for a pressurized system both without CO 2 capture [42].…”
Section: Competing Technologies Significant Issues and Future Directmentioning
confidence: 99%
“…A DCFC can use the existing electrolyte mixture commonly used in molten carbonate fuel cell (MCFC) systems [1]. A performance improvement could be attained by means of better contact between the coal particles, electrolyte mixture and anode.…”
Section: Introductionmentioning
confidence: 99%